2014 7th Advanced Satellite Multimedia Systems Conference and the 13th Signal Processing for Space Communications Workshop (ASM 2014
DOI: 10.1109/asms-spsc.2014.6934540
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of channel codes in presence of pulsed jammers in TT&C links

Abstract: This paper compares different channel coding schemes, such as the short Low-Density Parity-Check (LDPC) proposed by NASA for TC applications, and Reed Solomon (RS) codes, in presence of pulsed jammers that causes burst errors. The burst error patterns are generated also considering the occurrence of cycle slips due to the pulsed jammers. Moreover, the effectiveness of introducing interleavers of different depths is investigated for both channel codes. The comparison shows that RS codes represent a robust solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…With a view of increasing the robustness of satellite telecommand (TC) links against jamming, the planned next‐generation TC systems adopt direct‐sequence spread‐spectrum (DSSS) modulation with a very long pseudo‐noise (PN) spreading code repetition period and a high spreading factor, along with advanced channel coding . In previous studies,() the codeword error rate (CER) performances of the recommended coding schemes have been investigated under DSSS modulation in the presence of jamming, assuming perfect chip, carrier, symbol, and frame synchronization.…”
Section: Introductionmentioning
confidence: 99%
“…With a view of increasing the robustness of satellite telecommand (TC) links against jamming, the planned next‐generation TC systems adopt direct‐sequence spread‐spectrum (DSSS) modulation with a very long pseudo‐noise (PN) spreading code repetition period and a high spreading factor, along with advanced channel coding . In previous studies,() the codeword error rate (CER) performances of the recommended coding schemes have been investigated under DSSS modulation in the presence of jamming, assuming perfect chip, carrier, symbol, and frame synchronization.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the new issue of the CCSDS satellite TC synchronization and channel coding sublayer protocol, published in September 2017, has introduced a novel communication link transmission unit (CLTU) structure with advanced LDPC channel coding. It has been shown that, under perfect synchronization, these codes can offer an increased resilience against jamming. In practice, however, a system is never a priori synchronized, and the structures that are in place to perform synchronization are themselves susceptible to jamming attacks.…”
Section: Introductionmentioning
confidence: 99%
“…with Π (z) (x, y) the probability that x hard decision errors occur when z out of y observed bit intervals are jammed, defined in (3).…”
Section: B False Alarm Probabilitymentioning
confidence: 99%
“…To increase the resilience of satellite telecommand (TC) links against jamming, next generation TC systems are planning to adopt direct-sequence spread spectrum (DSSS) modulation with a very long pseudo-noise spreading code repetition period and a high spreading factor [1], along with advanced channel coding [2], [3].…”
Section: Introduction and State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation